Factors Affecting Tax Compliance with the Complexity of Tax Regulations as a Moderator Variable - Welly Chandra; Waluyo (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The aim of this study was to determine the role of Understanding of Tax Regulations and E-Filling Service Quality in explaining Tax Compliance of tax payers with certain business in Jakarta and determining moderating effects of Tax Regulation Complexity. The samples used in this study are tax payers of certain business in Jakarta. This research is a research with descriptive research design and the sample of this research collected from 146 respondents who are individual tax payers with certain business in Jakarta. This respondents selected by using convenience sampling method. Data analysis technique study indicated that Understanding of Tax Regulations don’t have significance influence on explaining Tax Compliance but E-Filling Service Quality have positive influence on Tax Compliance and Tax Regulation Complexity didn’t have any moderating effect on the relation of Understanding of Tax Regulation on Tax Compliance but have moderating effect on relationship between E-Filling Quality Service and Tax Compliance.